Factors contributing to work environment improvement : a case study of Sekolah Menengah Kebangsaan Ahmad Boestamam, Sitiawan, Perak / Mazlan Che Soh, Mohd Fadzli Abdul Latif and Nazatulliani Mohd Sharif - Che Soh, Mazlan; Abdul Latif, Mohd Fadzli; Mohd Sharif, Nazatulliani (Universiti Teknologi MARA, Shah Alam, 2010)
Work environment surrounding in the organization brings many positive and negative effects to the employees. This situation may affect their performance while doing the job. Environmental become one of the important factor that contribute to the employees improvement. This factor also affects the organization as a whole. The study examines the most significant factors that contributing to the work environment improvement among teachers. A random sample of 100 teachers in Sekolah Menengah Kebangsaan Ahamd Boestamam, Sitiawan, Perak, were interviewed on two major issues. The teacher's level of perception and factors contributing to work environment improvement were examined. The study provided strong evidence, which shows that work environment bring, an important aspect to teacher's environment improvement. The factors of management commitment, empowerment and rewards bring a positive relationship with work environment improvement among teacher. The most significant factor towards the work environment improvement among teacher is management commitment even though the percentage is low but there are positive relationship and significant exist.